Maximizing the Benefits of Reclaimed Water for Irrigating the Landscape and Protecting the Environment - George Hochmuth; Laurie Trenholm; Don Rainey; Esen Momol; Claire Lewis; Brian Niemann (EDIS)
Reclaimed water is water that has been treated in municipal wastewater facilities and is safe to use for designated purposes, including residential landscape irrigation. “Water reuse” is the term used to describe the beneficial application of reclaimed water. Approximately 663 million gallons of reclaimed water are used daily in Florida. Florida is a national leader in using reclaimed water, and in 2006 Florida’s reuse program received the first U.S. Environmental Protection Agency Water Efficiency Leader Award. Using reclaimed water in Florida meets a state objective for conserving freshwater supplies, and preserves the water quality of rivers, streams, lakes, and aquifers. This publication discusses the benefits of using reclaimed water to irrigate the landscape and explains how using reclaimed water helps to protect the environment. This 4-page fact sheet was written by George Hochmuth, Laurie Trenholm, Don Rainey, Esen Momol, Claire Lewis, and Brian Niemann, and published by the UF Department of Soil and Water Science, November 2013. http://edis.ifas.ufl.edu/ss587